A novel approach to remote sensing of vegetation - Bidyuk, P.I.; Litvinenko, V.I.; Ponomarenko, S.O. (Навчально-науковий комплекс "Інститут прикладного системного аналізу" НТУУ "КПІ" МОН та НАН України, 2005)
The problem of remote estimation of chlorophyll content in vegetation is considered. Some reflectance spectra have been recorded for winter wheat leaves with various level of chlorophyll concentration. To reduce the level of noise in the measurement data produced by measuring system and possible influence of soil surface smoothing procedure proposed by Savitzky and Golay was applied. The 1st derivative of reflec-tance spectra curves had been computed and analyzed with respect to correlation with pigment content. To compute an estimate of chlorophyll content multiple re-gression as well as neural net approach have been applied and both proved to be successful. Pозглянуто проблему оцінювання концентрації хлорофілу в рослинах. Проведено експерименти з метою запису відбитих спектрів для озимої пшениці з різними значеннями вмісту хлорофілу. Побудовано графіки перших похідних та виконано аналіз вмісту пігменту. Для зменшення рівня шумів експериментальних даних використано процедуру згладжування, запропоновану Савицьким і Голеєм, яка базується та 9-точковій згортці. Для оцінювання вмісту хлорофілу успішно застосовано лінійну множинну регресію та нейронні мережі. Рассмотрена проблема оценивания концентрации хлорофилла в растениях. Проведены эксперименты с целью записи отраженных спектров для озимой пшеницы с различными значениями содержания хлорофилла. Построены графики первых производных и выполнен анализ содержания пигмента. Для уменьшения уровня шумов экспериментальных данных использована процедура сглаживания, предложенная Савицким и Голеем, которая основывается на 9-точечной свертке. Для оценивания содержания хлорофилла успешно применена множественная регрессия и нейронные сети.